Cognitive decline and healthy aging: an online activities and psychoeducational program for older adults in the context of COVID-19 Pandemic: preliminary results - Feldberg, Carolina (2021)
AbstractBackground: The preventive and compulsory social isolation regulations due to COVID-19 affected the entire population, but this became more emphasized in the group of older adults. Many older adults who attended workshops, retirement centers and clubs had to interrupt their activities. This has impacted negatively on their activity level, socialization, and emotional state. The aim of the present study is to present preliminary results of the implementation of an online activities and psychoeducational program to prevent cognitive decline and promote healthy aging habits on older adults who live in Argentina in the context of Covid-19 Pandemic.Method. Design: Descriptive study. Subjects: 396 self-validated older adults, male and female. Instruments: socio-demographic and social participation questionnaire. Procedure: The intervention consists of a series of workshops (yoga, meditation, gym, singing lessons, memory, preparation for retirement and reflection about grief) and monthly specialist ´s talks on different topics about healthy aging. All the activities where done through zoom platform. All participants where offer one to one capacitation and written material about how to use this platform. Older adults could choose in how many activities they would take part in.Results. Data of 396 older adults who have taken part in the on-line version of the program on 2020 indicate that median age was 70.66 years old (ds= 8,7) of which 86 % were women. 79 % took part in specialists talks and 68 % on workshops and talks.Discussion: These results provide empirical evidence regarding the need to implement online intervention programs for older adults. Participating in an online educational program could increase participant?s cognitive healthy habits literacy, empowerment and engagement in brain health promotion activities, which in turn could reduce their dementia risk and feeling of loneliness in pandemic context.